Mothers’ Knowledge about Diaper Rash and Preventive Measures in Bangladesh - Sadique, Zahir; Begum, Nurunnahar Fatema; Sarker, Md Ferdousur Rahman; Bhuyian, Md Nazmul Islam; Md Kamruzzaman, - (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Use of disposable diapers by parents for their children has grown in last few decades. Although, most of the time diaper rash is not life threatening, it is a concern for the parents, and uncomfortable and painful for children Objectives: To measure the knowledge and practice of mothers when diapering and administering perineal care to infants wearing disposable diapers and factors that can influence the frequency of the occurrence of diaper rash in children between 0-12 months in Bangladesh. Methods: This cross-sectional study was conducted during the outpatient visits of mothers and their infants at the Combined Military Hospital located in Cumilla, Bangladesh between 01 February 2015 and 31 July 2015 with their infants. A structured, self-completed, closed-ended questionnaire was provided to 110 mothers who came to visit the Pediatric outdoors. Results: Thirty-seven (33.64%) infants aged one or under were reported to have experienced diaper rash during or prior to enrolment in the study. Study analysis showed that the risk of diaper rash was significantly higher in babies who used only 1-2 diapers/day than for babies who used more than 4 diapers/day (40.0% vs 21.43%). Infants whose mothers had knowledge of the causes and preventions of diaper rash and/or who received information about the importance of the proper cleaning of the diaper area during diaper changes suffered fewer incidents of diaper rash than those whose mothers did not (24% vs 36.48%). The causes of diaper rash were described by 48.65% mothers as heat followed by 27.03% mothers by frequent stool/urine. Conclusion: Frequently changing disposable diapers and cleaning the diaper area thoroughly can reduce cases of diaper rash dramatically in children less than one year old. The knowledge of mothers regarding diaper rash is an important factor in reducing diaper rash in their children. DS (Child) H J 2020; 36(1) : 39-45